Potential distribution of Puya raimondii Harms in future climate change scenarios - Quispe Rojas, Wilder Rolando (2020)
The anthropogenic climate change is a major cause of biodiversity loss. In this context, there is a need for studies based on the future impacts of large-scale climate change to propose conservation strategies for endangered species such as Puya raimondii Harms, a species of bromeliad endemic to the Andes of Peru and Bolivia. In this article, we model the current and future potential distribution of P. raimondii in order to identify priority areas for the future conservation of this endemic species. Our results revealed that 1) the current potentially suitable areas are centered in the Andes of Peru and Bolivia with an extension of 154268.40 km², and 2) in future climate change scenarios for the 2070s, there is a loss of potential areas, with an average reduction of area to -34326.53 km² and -8193.22 km² for the two climate scenarios of Representative Concentration Pathways (RCP) 4.5 and RCP 8.5 respectively. These results suggest that under climate change scenarios only five habitat patches will be suitable to host P. raimondii, therefore we propose that conservation measures should be prioritized to these areas.